2007
DOI: 10.1590/s0102-311x2007000500007
|View full text |Cite
|
Sign up to set email alerts
|

Resistência do Mycobacterium tuberculosis às drogas em pacientes HIV+ em cinco municípios da Baixada Santista, São Paulo, Brasil

Abstract: No início dos anos 90, observou-se aumento da resistência do Mycobacterium tuberculosis às drogas antituberculose, com alta prevalência entre pacientes HIV+. Neste estudo, foram avaliados a freqüência de resistência, o perfil de sensibilidade do M. tuberculosis às drogas e os fatores predisponentes à resistência entre indivíduos HIV+ nos municípios de Santos, São Vicente, Cubatão, Praia Grande e Guarujá, Estado de São Paulo, Brasil. Foram pesquisados os prontuários de 301 pacientes com resultado de cultura pos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
8
0
6

Year Published

2008
2008
2012
2012

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(15 citation statements)
references
References 29 publications
1
8
0
6
Order By: Relevance
“…Such a finding deserves comment. The prevalence of TB-HIV co-infection in MDR-TB cases in our study was higher than that reported in other studies conducted in SP (Melo et al 2003, Telles et al 2005), but was similar to that found in another study in the metropolitan area of Santos (Rozman et al 2007). These inconsistencies may be explained by the fact that Santos is a port city and has one of the highest rates of HIV/AIDS in SP (SES 2010).…”
Section: Discussionsupporting
confidence: 85%
“…Such a finding deserves comment. The prevalence of TB-HIV co-infection in MDR-TB cases in our study was higher than that reported in other studies conducted in SP (Melo et al 2003, Telles et al 2005), but was similar to that found in another study in the metropolitan area of Santos (Rozman et al 2007). These inconsistencies may be explained by the fact that Santos is a port city and has one of the highest rates of HIV/AIDS in SP (SES 2010).…”
Section: Discussionsupporting
confidence: 85%
“…Considering the magnitude of TB as a public health issue, the economic importance of the city of Santos and the few published studies addressing this issue, (5) we aimed to describe the behavior of pulmonary TB (PTB) in the city of Santos, based on data obtained from the TB surveillance database. The principal objectives of the present study were to estimate incidence rates, mortality rates, retreatment rates and hospitalization rates, as well as the principal treatment outcomes (treatment abandonment, cure and death).…”
Section: Introductionmentioning
confidence: 99%
“…2007; Davoudi et al. 2008), CD4 + lymphocyte cell counts do not always correlate with the chance of developing tuberculosis, as observed for other infectious diseases (Rozman et al. 2007).…”
Section: Discussionmentioning
confidence: 79%
“…This points to the need of establishing measures of local hospital mycobacteria surveillance, because HB as the regional reference centre for HIV/AIDS diagnosis and treatment deals with a great number of potentially TB‐co‐infected patients. Although tuberculosis is the most common opportunistic infection in HIV‐seropositive persons and CD4 + T lymphocytes are most important in the protective response against M. tuberculosis (Rozman et al. 2007; Davoudi et al.…”
Section: Discussionmentioning
confidence: 99%